2009
DOI: 10.4314/ari.v5i2.48750
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Urinary Tract Infections (UTI) in sexually active women of Abakaliki, Ebonyi State, Nigeria

Abstract: A research to investigate the prevalence of urinary tract infections in sexually active women (18-41 years) from selected health care centres in Abakaliki was carried out. Attempt was made to fined out the number of treated cases, aetiologic agents and age range with highest inc dence o urinary tract infections over the study period (2004-2005). Medical records of urinary tract infected women from the selected health care centres were reviewed. The prevalence of urinary tract infections was high (1232) among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This is in agreement with other studies showed that other physiological changes during pregnancy such as hormonal changes provide the ideal environment for UTI-causing bacteria (E. coli) and increase rate of infection, likewise vagina of the pregnant women work as niche for bacterial and Candida growth due to moisture habitat and rich glycogen content [59]. Also sexually active women are more susceptible to UTI [60]. Therefore, all these factors will increase rate of UTI infection in women more than men.…”
Section: Discussionsupporting
confidence: 80%
“…This is in agreement with other studies showed that other physiological changes during pregnancy such as hormonal changes provide the ideal environment for UTI-causing bacteria (E. coli) and increase rate of infection, likewise vagina of the pregnant women work as niche for bacterial and Candida growth due to moisture habitat and rich glycogen content [59]. Also sexually active women are more susceptible to UTI [60]. Therefore, all these factors will increase rate of UTI infection in women more than men.…”
Section: Discussionsupporting
confidence: 80%
“…Those with ages less than 20 years had the lowest infection (13.7%). The high rate of UTI among the age category 20-39 years could be due to the high incidence of sexual activity and/or multiple sex partners known to be associated with that age group [ 24 ]. UTI among patients within the age range of 40-59 (12.6%) and above 60 years (15%) observed in this study could be due to factors such as prostatic enlargement in males, reduced ambulation, catheterization, diabetes mellitus and weak bladder sphincters [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infections can occur in any portion of these structures, but bladder and urethra infections are the most prevalent (2). women have a higher rate of UTIs than other healthy women in the general community (3).…”
Section: Introductionmentioning
confidence: 99%